Аctual modeling process in teaching foreign languages at non-language higher educational institution - Julia D. Yermakova; Natalya V. Kulikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the current methodological possibilities of modeling the process of learning a foreign language using innovative models, computer technology, interactive development, appearing with the expanding capabilities of the Internet, informatization and computerization of society. The particular importance in this regard is the problem of choosing the optimal innovation technologies, which is solved by the identification of the key components The Internet is not only an indispensable source of information, but also a mean of interactive learning. The modeling process provides a possibility to choose optimal innovative technologies, due to which we can improve the entire educational process. Modern possibilities to model the process of teaching foreign languages can be interesting not only to specialists in the field of education and linguistics, but to all those who wish to maintain or improve their proficiency level in foreign languages.